Freirean Pedagogy in Beirut’s Migrant Worker Classroom - Shireen Keyl (Pedagogy & (Im)Possibilities across Education Research, 2017)
This article is based on a three-month ethnographic study conducted in a non-governmental organization (NGO) in Beirut, Lebanon. This particular NGO, in conjunction with other organizations, provides educational opportunities for migrant domestic workers: adult language classes for learning English and French. The volunteer teachers have no pedagogical or instructional training, and often no previous teaching experience. By way of participant observation and in-depth interviews, I examine the narratives of volunteer teachers who describe a Freirean pedagogical position that is also evident in their teaching practices. I assert that a Freirean model for NGO functionality can bring about liberatory and transformative education and a successful NGO structure.
Keywords: Paulo Freire; Non-governmental organization; Beirut; Lebanon; Transformative education; Migrant domestic workers